2011
DOI: 10.1155/2011/126240
|View full text |Cite
|
Sign up to set email alerts
|

Serum Progranulin as an Independent Marker of Liver Fibrosis in Patients with Biopsy-Proven Nonalcoholic Fatty Liver Disease

Abstract: Background: Elevated progranulin levels are associated with visceral obesity, elevated plasma glucose, and dyslipidemia. Progranulin has not been previously investigated as a biomarker of nonalcoholic fatty liver disease (NAFLD). We sought to determine whether serum progranulin levels are altered in patients with biopsy-proven NAFLD and if they are associated with their clinical, biochemical, and histological characteristics. Subjects and methods: We measured serum progranulin levels in 95 patients with biopsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 18 publications
0
30
1
Order By: Relevance
“…In fact, serum PRGN level showed a significantly positive correlation with serum IL-6 level in humans [13,14]. It was reported that serum PRGN levels were higher in patients with non-alcoholic fatty liver disease, and their levels were correlated with liver fibrosis [21]. In this study, however, there was no difference in serum PRGN level between hepatic steatosis and nonhepatic steatosis.…”
Section: Discussioncontrasting
confidence: 60%
“…In fact, serum PRGN level showed a significantly positive correlation with serum IL-6 level in humans [13,14]. It was reported that serum PRGN levels were higher in patients with non-alcoholic fatty liver disease, and their levels were correlated with liver fibrosis [21]. In this study, however, there was no difference in serum PRGN level between hepatic steatosis and nonhepatic steatosis.…”
Section: Discussioncontrasting
confidence: 60%
“…Moreover, a recent study identified progranulin as a key adipokine that triggers systemic insulin resistance, adipocyte hypertrophy, and obesity through production of IL-6 in adipose tissue [9]. Previously, we also reported that circulating progranulin concentration has a significant positive correlation with systemic inflammatory markers such as hsCRP and IL-6 [22] and Yilmaz et al [23] showed that progranulin is significantly higher in nonalcoholic fatty liver disease patients than in controls, and progranulin expression correlates with the degree of hepatic fibrosis.…”
Section: Discussionmentioning
confidence: 84%
“…In an immunohistochemical analysis of human carotid endarterectomy specimens, both macrophages and vascular smooth muscle cells in atherosclerotic plaque express progranulin [17]. Yilmaz et al reported that patients with non-alcoholic fatty liver disease (NAFLD) have higher serum progranulin concentrations, which are positively associated with total cholesterol and LDL-cholesterol [35]. Recently, Qu et al reported that plasma progranulin levels were higher in Chinese patients with type 2 diabetes and correlated with insulin resistance, inflammation and glycolipid metabolism [36].…”
Section: Discussionmentioning
confidence: 99%